The spontaneous destabilization of neoclassical tearing mode with existing energetic ions in low torque tokamak plasmas. (30th August 2017) - Li, Erzhong; Hu, L.; Zhao, H.; Shi, T.; Liu, Y.; Liu, H.; Zhang, J.; Xu, L.
Abstract: Periodic destabilization of a neoclassical tearing mode (NTM, m / n   =  2/1) in between two edge localized modes (ELMs) is observed with a varying frequency that deviates from the wave-particle resonance determined precession frequency, is instead near the electron diamagnetic drift frequency. This scenario is created by the balanced injection of co- and counter-current neutral beams which give rise to low-torque plasmas with a high confinement on the experimental advanced superconducting tokamak (EAST). The destabilization is obviously dependent on the ratio of the mode frequency to the electron diamagnetic frequency, indicating the effect of relative rotation between the NTM and plasmas on the mode stability. In particular, the role of polarization current in general Rutherford equation is identified by experimental data reported in this letter.